Analysis of Domestic Water Availability and Demand As Well As The Economic Value Of Laabhalano Spring Pola Village, Pasir Putih District, Muna Regency - Jaluwi, La; Gandri, La; Kahirun, Kahirun; Teke, Junartin; Muhsimin, Muhsimin; Hidayat, Herlan (Journal of Soilscape and Agriculture, 2025)
Laabhalano Spring in Pola Village, Pasir Putih Subdistrict, Muna Regency, serves as the local community's primary source of clean water. However, the sustainability of this water source is under threat due to environmental degradation, such as deforestation and land-use changes, which could impact both the quality and quantity of the water. This study aims to analyze water availability, and domestic water demand, and assess the economic value of the environmental services provided by Laabhalano Spring. The methods used in this research include measuring the water flow and surveying domestic water needs in 82 households in Pola Village. The findings show that the water flow from Laabhalano Spring is 110,376 m³ per year, sufficient to meet the community’s domestic water needs. Total domestic water consumption is 330 m³ per month, primarily for bathing, washing, and daily consumption. Additionally, the economic value of this clean water service is estimated to be IDR 137,700,000 per year, highlighting the critical role of this spring for the local community’s livelihood. While the current water flow is adequate, the threat to the sustainability of the spring remains, especially if the surrounding ecosystem is not properly managed. Therefore, sustainable environmental management is essential to ensure a continuous clean water supply for the residents of Pola Village. Strengthening conservation efforts and monitoring the surrounding environment are key to preserving both the quality and availability of water in the future